New Insights of Corynebacterium kroppenstedtii in Granulomatous Lobular Mastitis based on Nanopore Sequencing. Issue 3 (7th February 2022) - Li, Xin-Qian; Yuan, Jing-Ping; Fu, Ai-Si; Wu, Hong-Li; Liu, Ran; Liu, Tian-gang; Sun, Sheng-Rong; Chen, Chuang
Abstract: Background: The etiology of granulomatous lobular mastitis (GLM) remains unknown. This study aimed to detect bacteria in GLM using Nanopore sequencing and identify the relationship between GLM and Corynebacterium kroppenstedtii . Methods and materials: The bacterial detection on fresh samples (including breast pus and tissue) of 50 GLM patients using nanopore sequencing and culture methods. The bacterial detection rate of participants with different stages were compared and analyzed. Formalin-fixed and paraffin-embedded (FFPE) tissues from 39 patients were performed on Gram staining to identify Gram-positive bacilli (GPB) within lipid vacuoles. Moreover, the clinicopathological characteristics of GLM patients in different bacterial subgroups were also conducted. Results: In 50 GLM patients, the detection rate of bacteria was 78% using nanopore sequencing method, especially in the early stage of GLM (over 80%), which was significantly higher than that using culture methods (24%, p  < 0.001). The dominant bacteria were Corynebacterium species (64%), especially for the Corynebacterium kroppenstedtii . The detection rate of C. kroppenstedtii in nanopore sequencing method (56%) was higher than that in culture methods (16%, p  < 0.001). Gram staining positive of bacteria in 7 patients, and 5 of them were C. kroppenstedtii . Thirty-one patients (31/39, 79.5%) exhibited typical histological structure of cystic neutrophilic granulomatous mastitis (CNGM), and eighteen patients detected with C. kroppenstedtii . Conclusion: Nanopore sequencing showed rapid and accurate bacteria detection over culture method in GLM patients. GLM is not sterile inflammation and closely related to C. kroppenstedtii . CNGM was associated with Corynebacterium infection, especially for C. kroppenstedtii .